Physico-chemical and sensory properties of bread enriched with lemon pomace fiber - Rei-Chu CHANG; Chia-Yen LI; Sy-Yu SHIAU (Czech Journal of Food Sciences, 2015)
Lemon fiber (LF) was extracted from lemon pomace and incorporated into bread. The results showed that the hardness of bread increased with the increase of LF substitution (0-9%), but the cohesiveness, springiness, and specific volume decreased with the fiber substitution. Both Peleg-Normand and Wiechert models fitted well the stress relaxation data of bread. The parameters (k1 and k2, as well as P0-P2 and λ2) in two models were followed significantly affected by the amount of LF. The breads enriched with LF revealed higher total phenolic contents and DPPH radical scavenging capacities than the control bread. Compared with water, methanol was a better solvent for extracting total phenolic compounds of bread. These results suggest that the addition of 3% LF can produce healthy and acceptable bread with higher phytochemicals and antioxidant capacities.